Advances in Functional Inorganic Materials Prepared by Wet Chemical Methods - Zarkov, Aleksej; Kareiva, Aivaras; Tamasauskaite-Tamasiunaite, Loreta (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Functional inorganic materials are an indispensable part of innovative technologies that are essential to the development of many fields of industry. The use of new materials, nanostructures, or multicomponent composites with specific chemical or physical properties promotes technological progress in electronics, optoelectronics, catalysis, biomedicine, and many other areas that are concerned with many aspects of human life. Due to the broad and diverse range of potential applications of functional inorganic materials, the development of superior synthesis pathways, reliable characterization, and a deep understanding of the structure-property relationships in materials are rightfully considered to be fundamentally important scientific issues. Only synergetic efforts of scientists dealing with the synthesis, functionalization and characterization of materials will lead to the development of future technologies.